2017
DOI: 10.1371/journal.pone.0174853
|View full text |Cite
|
Sign up to set email alerts
|

Differential inhibition of activity, activation and gene expression of MMP-9 in THP-1 cells by azithromycin and minocycline versus bortezomib: A comparative study

Abstract: Gelatinase B or matrix metalloproteinase-9 (MMP-9) (EC 3.4.24.35) is increased in inflammatory processes and cancer, and is associated with disease progression. In part, this is due to MMP-9-mediated degradation of extracellular matrix, facilitating influx of leukocytes into inflamed tissues and invasion or metastasis of cancer cells. MMP-9 is produced as proMMP-9 and its propeptide is subsequently removed by other proteases to generate proteolytically active MMP-9. The significance of MMP-9 in pathologies tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 54 publications
3
26
0
1
Order By: Relevance
“…Interestingly, doxycycline, an antibiotic analogue of tetracycline, reduced CD147 levels in a gallbladder carcinoma cell line [19] and gingival crevicular fluid (soluble form) in patients with chronic periodontitis [20]. In addition, monocytes and peripheral blood mononuclear cells treated with azithromycin expressed less MMP-9 [21,22], as well as airways of lung transplant patients did upon treatment with azithromycin [23]. Furthermore, MMP-3 and MMP-1 expression was reduced in respiratory epithelial cells in vitro following azithromycin treatment [24].…”
Section: Cd147 As a Target For Covid-19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, doxycycline, an antibiotic analogue of tetracycline, reduced CD147 levels in a gallbladder carcinoma cell line [19] and gingival crevicular fluid (soluble form) in patients with chronic periodontitis [20]. In addition, monocytes and peripheral blood mononuclear cells treated with azithromycin expressed less MMP-9 [21,22], as well as airways of lung transplant patients did upon treatment with azithromycin [23]. Furthermore, MMP-3 and MMP-1 expression was reduced in respiratory epithelial cells in vitro following azithromycin treatment [24].…”
Section: Cd147 As a Target For Covid-19 Treatmentmentioning
confidence: 99%
“…Furthermore, MMP-3 and MMP-1 expression was reduced in respiratory epithelial cells in vitro following azithromycin treatment [24]. In fact, several studies have demonstrated that azithromycin decreases MMP expression and action [21][22][23][24]. Despite CD147 and MMPs are closely related molecules, further studies are necessary to evaluate whether azithromycin directly changes expression levels of the CD147 receptor.…”
Section: Cd147 As a Target For Covid-19 Treatmentmentioning
confidence: 99%
“…The presence of these O -linked glycans increases the domain flexibility of MMP9, allowing the protease to adopt multiple enzyme conformations and facilitating individual movements of the catalytic and the hemopexin domain. This influences the recognition, binding, and processing of substrates, cell receptors, and endogenous inhibitors [62,63]. A study by den Steen et al described that the OG domain is indispensable for correct orientation of the hemopexin domain for MMP9 internalization and degradation by LRP-1 and LRP-2, as well as inhibition by endogenous TIMP1 [60].…”
Section: Ptms—an Additional Level Of Protein Regulationmentioning
confidence: 99%
“…We recently demonstrated that the matrix metalloproteinase MMP-9 is the key protease involved in histone H3 tail cleavage during osteoclast differentiation [6]. Since tetracycline analogs are known to act as MMP-9 inhibitors [19,20], studying their possible effects on MMP-9-mediated H3 tail proteolysis was a logical extension of our study. To this end, we first attempted to identify the optimal inhibitor(s) of MMP-9 from the four tetracyclines currently in use.…”
Section: Resultsmentioning
confidence: 85%